Thermal-terminal anastomosis of the parotid duct - Pacheco G., Ignacio Vicente (Revista Universidad de Guayaquil, 1990)
This case presented leads us to think about the importance, both from an aesthetic and functional point of view, of the parotid gland and its conservation through the end-to-end anastomosis of the Stensen duct with a really simple surgical procedure already described, since the Parotidectomy as a surgical procedure commonly carried out in these cases, has resulted in facial asymmetry, facial paresis, xerostomia, etc.
Keywords: Digestive; Protective